Impact of temperature on the growth of Pseudomonas spp. (SUBP01), Bacillus spp. (SUBB01) and Salmonella spp. (SUBS01) and determination of the critical growth temperature (Bangladesh Journal of Microbiology, 2019)
With a previous observation of the defensive response against elevated temperatures and nutrient variation in Escherichia coli in different culture media, present study further demonstrated the consequences of high temperature on the growth of Pseudomonas spp. (SUBP01) Bacillus spp. (SUBB01), and Salmonella spp. (SUBS01). Bacterial growth was measured through the enumeration of the viable and culturable cells on Luria-Bertani (LB) and nutrient agar (NA) plates up to 72 hours, microscopic experiments were conducted to monitor subsequent physiological changes, and finally the loss of culturability due to high temperature stress was further confirmed by the observation of growth incapability through spot tests. A slight reduction in the culturable cells of Pseudomonas spp. (SUBP01) was observed at 45°C after 24 to 72 hours of incubation in the LB media while no such inhibition of growth was noticed in the nutrient media. Notably, Bacillus spp. and Salmonella spp. remained uninfluenced up to 52°C in both media, suggestive of the existence of a stringent defense mechanism against heat shock in these bacterial cells. However, both Bacillus and Salmonella cells were found to lose their culturablility completely at 53°C, and hence the critical temperature were recorded to be 52°C both for Bacillus spp. (SUBB01) and Salmonella spp. (SUBS01) while 45°C for Pseudomonas spp. (SUBP01) cells. Interestingly, the recovery of cells was noticed upon supplementation of Mg2+ and ethylene diamine tetra acetic acid (EDTA) through the increase in the viable and culturable cells at heat stressed condition. Consequently, all 3 bacterial species were subjected to transient heat shock by temperature up-shifting from 37°C to 45°C and 30 °C to 47°C in order to justify the bacterial heat shock response in the phenotypic state, whereby Pseudomonas spp. (SUBP01) cells were found lose culturability by temperature up-shifting from 30°C to 47°C, while Salmonella spp. (SUBS01) and Bacillus spp. (SUBB01) cells remained uninfluencedBangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 55-62